Venezuelan equine encephalitis virus in Iquitos, Peru: urban transmission of a sylvatic strain. - Amy C Morrison; Brett M Forshey; Desiree Notyce; Helvio Astete; Victor Lopez; Claudio Rocha; Rebecca Carrion; Cristhiam Carey; Dominique Eza; Joel M Montgomery; Tadeusz J Kochel (Public Library of Science (PLoS), 2008)
Enzootic strains of Venezuelan equine encephalitis virus (VEEV) have been isolated from febrile patients in the Peruvian Amazon Basin at low but consistent levels since the early 1990s. Through a clinic-based febrile surveillance program, we detected an outbreak of VEEV infections in Iquitos, Peru, in the first half of 2006. The majority of these patients resided within urban areas of Iquitos, with no report of recent travel outside the city. To characterize the risk factors for VEEV infection within the city, an antibody prevalence study was carried out in a geographically stratified sample of urban areas of Iquitos. Additionally, entomological surveys were conducted to determine if previously incriminated vectors of enzootic VEEV were present within the city. We found that greater than 23% of Iquitos residents carried neutralizing antibodies against VEEV, with significant associations between increased antibody prevalence and age, occupation, mosquito net use, and overnight travel. Furthermore, potential vector mosquitoes were widely distributed across the city. Our results suggest that while VEEV infection is more common in rural areas, transmission also occurs within urban areas of Iquitos, and that further studies are warranted to identify the precise vectors and reservoirs involved in urban VEEV transmission.